2013
DOI: 10.1021/jo401706r
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Herbicidin C and Aureonuclemycin: Impasses and New Avenues

Abstract: The undecose nucleoside antibiotics herbicidin C and aureonuclemycin are biologically highly active and represent challenging targets for total synthesis. Herein, the gradual evolution of our synthetic strategy toward these natural products is described in detail. The initial route encompasses metalate addition chemistry but suffers from poor stereochemical control. In contrast, the ultimately successful strategy benefits from a variety of reagent-controlled stereoselective transformations, including a surpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…With 1,6-anhydroglucose possessing the same oxidation state as glucose, no reduction step would be required, in contrast to the gluconolactone approach. While the relative inertness of the 1,3-dioxolane ring of 2 rendered non-Lewis acid assisted nucleophilic attack unviable, literature precedent for the allylation of 2,3,4-tri- O -benzyl-1,6-anhydroglucose ( 2 : PG = Bn) in the presence of BF 3 ·OEt 2 or TMSOTf suggested that Lewis acid assisted nucleophilic attack would be possible but would favor the undesired α-anomer. To mitigate this, the requisite aryl nucleophile and a Lewis acid could be combined into a single agent able to (i) coordinate to and open the 1,3-dioxolane ring of compound 2 to furnish an oxocarbenium ion and, (ii) while covalently bound to the C6 oxygen as an ate complex of the opened 1,3-dioxolane ring, deliver the aryl anion directly to the requisite β-face of the oxocarbenium ion, thereby furnishing the desired β- C -arylglucosides 4 .…”
Section: Introductionmentioning
confidence: 99%
“…With 1,6-anhydroglucose possessing the same oxidation state as glucose, no reduction step would be required, in contrast to the gluconolactone approach. While the relative inertness of the 1,3-dioxolane ring of 2 rendered non-Lewis acid assisted nucleophilic attack unviable, literature precedent for the allylation of 2,3,4-tri- O -benzyl-1,6-anhydroglucose ( 2 : PG = Bn) in the presence of BF 3 ·OEt 2 or TMSOTf suggested that Lewis acid assisted nucleophilic attack would be possible but would favor the undesired α-anomer. To mitigate this, the requisite aryl nucleophile and a Lewis acid could be combined into a single agent able to (i) coordinate to and open the 1,3-dioxolane ring of compound 2 to furnish an oxocarbenium ion and, (ii) while covalently bound to the C6 oxygen as an ate complex of the opened 1,3-dioxolane ring, deliver the aryl anion directly to the requisite β-face of the oxocarbenium ion, thereby furnishing the desired β- C -arylglucosides 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of their complex chemical structures and diverse biological activities, HBCs have attracted considerable attention as targets for chemical synthesis. However, the biosynthetic pathways for HBCs were unknown until a recent report that described the identification of the biosynthetic gene cluster (BGC) her in Streptomyces sp. L-9-10 and the initial characterization of the biosynthetic pathway for HBC A ( 1 ) .…”
mentioning
confidence: 99%
“…Treatment of 1,6-anhydroglucose 805 with i -Bu 2 AlH followed by addition of aryl­(chloro)­alane 806 at 140 °C led to the opening of the 1,3-dioxolane ring and the formation of an ate complex between aryl­(chloro)­alane and the C-6-oxygen of the sugar derivative, which underwent β-face attack on the oxocarbenium ion to furnish canagliflozin 807 in 50% isolated yield with excellent β-selectivity (Scheme ). ,, TiCl 4 -mediated reaction of 2,7-dioxabicyclo[2.2.1]­heptane 808 with allyltributylstannnane gave 2,5- trans -disubstituted tetrahydrofuran 809 as the predominant product ( trans / cis = 93:7) in 84% yield (Scheme ). , C -Allylation of 1,2- O -isopropylidene furanose derivative 810 with allyltrimethylsilane under the promotion BF 3 ·OEt 2 probably proceeded through the inside attack of the stable oxocarbenium ion intermediate A , affording C -furanoside 811 with high 1,3- trans stereoselectivity in 65% yield (Scheme ).…”
Section: Synthesis Of C-glycosides With Miscellaneous Substratesmentioning
confidence: 99%